Caracterización Ornitológica, en estribaciones de la Cordillera Occidental de los Andes en los Bosques Montano, Montano Bajo y Piemontano, Sector La Esperanza y Recinto Los Laureles, parroquia El Tingo, Cotopaxi 2019. - Vichicela Albán, Alexis Bladimir (2019)
This research purpose is to gather information from the Ornitofauna of the Montano, Montano Bajo and Piemontano Forests in El Tingo placed in La Esperanza and Los Laureles enclosure, which is located in the foothill at Western Andes Mountains, in the western and temperate subtropical zoogeographic floor .The information collected are the first to be presented in the area, the methodological guide about Ornithofauna component of Environment Ministry was used as a reference for this research, the methods used to collect the information were: observation points, random routes, vocalizations recording, occasional captures with mist nets, photographic records, none of these methods were adjusted to a rigorous design or pre-established sampling time. From November 2018 to June 2019, 48 species were recorded, belonging to 11 orders and 24 families. One of these species is endemic to the western subtropical floor, 9 have high sensitivity to habitat alteration, 20 have medium sensitivity and 19 have low sensitivity. This area has been little explored and studied, its Ornithofauna is just beginning to be known, but the diversity and abundance found between 600 and 2200 meters above sea level is high. More in-depth studies with standardized methods are needed to know the details of these bird communities.